Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5505/agri.2013.98852
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin premedication for postoperative analgesia and emergence agitation after sevoflurane anesthesiain peadiatric patients.

Abstract: Gabapentin premedication decreases postoperative 24th hour analgesic consumption and attenuates emergence agitation after sevoflurane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
(46 reference statements)
3
11
0
Order By: Relevance
“…Postoperative analgesia was provided with intramuscular diclofenac sodium and intravenous morphine on demand, they found that preoperative administration of gabapentin reduced the intraoperative anesthetic requirements, blunted the hemodynamic response to intubation, and reduced the postoperative opioid consumption which is compatible with this study [16]. In other study by Akgün et al made a study on 46 healthy children aged 3-12 year old, they found that gabapentin premedication decreases postoperative 24 h analgesic consumption and attenuates emergence agitation after sevoflurane anesthesia which correspondent to this study [17].…”
Section: Discussionsupporting
confidence: 75%
“…Postoperative analgesia was provided with intramuscular diclofenac sodium and intravenous morphine on demand, they found that preoperative administration of gabapentin reduced the intraoperative anesthetic requirements, blunted the hemodynamic response to intubation, and reduced the postoperative opioid consumption which is compatible with this study [16]. In other study by Akgün et al made a study on 46 healthy children aged 3-12 year old, they found that gabapentin premedication decreases postoperative 24 h analgesic consumption and attenuates emergence agitation after sevoflurane anesthesia which correspondent to this study [17].…”
Section: Discussionsupporting
confidence: 75%
“…Gabapentin given as an oral premedication (15 mg kg À1 ) decreased the severity of EA in healthy children (3-12 yr) after a sevoflurane anaesthetic for adenotonsillectomy. 62 Melatonin Preoperative oral administration of melatonin (0.2 or 0.4 mg kg À1 ), despite it having no effect on preoperative anxiety, has been shown to have greater benefits than midazolam 0.5 mg orally in decreasing incidence of emergence delirium. A dose-dependent effect was found.…”
Section: Gabapentinmentioning
confidence: 99%
“…Colon cancer is a kind of tumor with a high morbidity rate in the elderly, which can be cured only by surgery (1)(2)(3)(4). To reduce the pain of patients during surgery, anesthetics need to be applied, but the cognitive ability will be prone to decline after general anesthesia in clinic, and immune dysfunction and other adverse reactions will be caused (5)(6)(7)(8). In order to avoid and reduce the occurrence of the above adverse reactions, therefore, it is particularly critical to choose anesthetics.…”
Section: Introductionmentioning
confidence: 99%